2019
DOI: 10.1002/adfm.201900084
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Specific Aptamer‐Conjugated Polymeric Photosensitizer for Effective Endo‐Laparoscopic Photodynamic Therapy

Abstract: Recent advances in medical technology and endo-laparoscopic devices have enabled the treatment of gastrointestinal (GI) cancers to be minimally invasive through endo-laparoscopic photodynamic therapy (PDT). To achieve an efficient regional or endo-laparoscopic PDT, it is necessary to develop a highly target specific photosensitizer (PS) that can be easily treated to the lesion site with endo-laparoscopic device. Here, an ideal polymeric PS is demonstrated for effective endo-laparoscopic PDT. In the synthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…And the X-ray photoelectron spectrum (XPS) of FeMn-LDH is presented in Figure S4 (Supporting Information), the Mn 2p 3/2 and Mn 2p 1/2 peaks at 634.4 and 654.5 eV demonstrate the presence of Mn 3+/4+ . [69,70] Simultaneously, the Fe 2p 3/2 and Fe 2p 1/2 located at 712.2 and 725.3 eV indicate the Fe is mostly in Fe 3+ oxidation state. [71] And the standard XRD pattern of β-NaGdF 4 (JCPDS No.…”
Section: Figure 1amentioning
confidence: 88%
“…And the X-ray photoelectron spectrum (XPS) of FeMn-LDH is presented in Figure S4 (Supporting Information), the Mn 2p 3/2 and Mn 2p 1/2 peaks at 634.4 and 654.5 eV demonstrate the presence of Mn 3+/4+ . [69,70] Simultaneously, the Fe 2p 3/2 and Fe 2p 1/2 located at 712.2 and 725.3 eV indicate the Fe is mostly in Fe 3+ oxidation state. [71] And the standard XRD pattern of β-NaGdF 4 (JCPDS No.…”
Section: Figure 1amentioning
confidence: 88%
“…Their small size allows them to be used for both surface biomarker recognition and intracellular targeting. In previous studies, aptamer-NP conjugates have certainly shown better tissue penetration [ 84 , 85 ]. Recently, Kim et al [ 85 ] developed a tumor-specific aptamer-conjugated polymeric PS for treating gastrointestinal cancer using an AS1411 aptamer, which binds to nucleolin on the membrane of cancer cells.…”
Section: Nanotechnology In Pdtmentioning
confidence: 99%
“…In previous studies, aptamer-NP conjugates have certainly shown better tissue penetration [ 84 , 85 ]. Recently, Kim et al [ 85 ] developed a tumor-specific aptamer-conjugated polymeric PS for treating gastrointestinal cancer using an AS1411 aptamer, which binds to nucleolin on the membrane of cancer cells. This compound was use in a laparoscopy-based PDT and their results showed enhanced and effective eradication of cancer cells under laser irradiation.…”
Section: Nanotechnology In Pdtmentioning
confidence: 99%
“…For the stability test of Rluc8 (or Rluc8.6) or its fusion proteins, 10 M protein was incubated in 1× PBS (pH 7.4) or undiluted normal mouse serum (Jackson ImmunoResearch, no. 015-000-001) for different time intervals (1,2,4,8,12,24, and 48 hours) at 37°C. The BL intensity of each reaction was measured using a GLOMAX Luminometer (Promega) immediately after treatment with 150 M Co-h.…”
Section: Protein Expression Purification and In Vitro Characterizationmentioning
confidence: 99%
“…In contrast to classical radiation or chemical therapy, PDT is characterized by the selective ablation of malignant cells, high tumor specificity, and minimal invasiveness. To expand its usefulness, many studies on PDT have explored the development of PS drugs alone or in combination with nanoparticle hybrids (3,4), immunostimulants (5,6), and/or other active targeting ligands (7,8). However, despite these achievements, several major challenges posed by the inherent properties of chemical PS drugs, such as in vivo accumulation and light penetration issues, limit their clinical effectiveness.…”
Section: Introductionmentioning
confidence: 99%